Clear water scour around submerged skewed bridge with and without pier - Farhangi, Amirsaeed (2016)
As recorded documents show, it is already less than a century that researchers have attempted to evaluate local scour depth around pier as a destructive phenomenon. Unfortunately, the climate changes and deforestation have changed and increased rainfall and runoff respectively in aggravated conditions to create inundated bridges. Therefore, in the last few decades, some other researchers have tried to predict scour depth under submerged bridge condition. Although their results are valuable, there are still different unstudied factors under submerged bridge condition which should be evaluated. One of the mentioned unstudied conditions is the effect of submerged skewed bridge on maximum scour depth and the present study endeavoured to determine this under clear water condition. Therefore, the main purpose of the present study is to experimentally improve existing equations about the prediction of maximum scour depth around the foundation of a submerged bridge with different angles between approaching flow and bridge deck alignments. In order to collect the required data, six different bridge models with and without pier with different angles of 0, 5, 10, 15, 22.5 and 30 degrees were used to evaluate the effect of bridge alignments on maximum scour depth. All models were tested for partially and fully submergence conditions using two different sizes of bed sediments with median sizes of 0.23 mm and 0.80 mm. A total of 48 runs were conducted. Analysis of collected data showed that deflection of approach flow along the skewed bridge thickness (girders and guard rail) is the main difference in comparison with the perpendicular approach flow direction. In actual fact, analysis of the approach flow velocity vector along the skewed bridge thickness showed that an unbalanced distribution of downward flow velocity occurred, which firstly caused unbalanced unit discharge along the upstream edge of the bridge without pier. Then, it made an unbalanced scour level along the downstream bridge edge. According to the mentioned mechanism, an equation based on mass conservation law was proposed to predict maximum scour depth with an acceptable root mean square error (RMSE) and mean absolute error (MAE) equal to 0.029 m and 0.023 m respectively. Also, a labyrinth flow between two sides of flume walls at the downstream of bridge may occur, in which its first direction is the most destructive direction toward the opposite flume wall, which is predicted by another obtained equation and changes from 34 degrees up to 65 degrees. But under submerged skewed bridge condition with pier, the existence of the pier caused maximum local scour depth around itself, and created vortices around the pier is much more than the deflection of flow along the submerged skewed thickness. Also, it was found that correction factor of pier alignment in submerged bridge is much less than the same condition in free flow. Then, relationship between dependent and independent variables firstly was determined. Finally, an equation was proposed by using dimensional analysis, collected data and multiple linear regressions with a better prediction amongst previous study with the least RMSE and MAE equal to 0.018 m and 0.014 m respectively. Also, correction factor of pier alignment in submerged bridge is almost 50% less than the same correction factor in free flow condition which was previously assumed the same. Both the proposed equations can acceptably predict maximum scour depth in comparison with the existing equations. Moreover, submergence ratios in both submerged bridge with and without pier show that maximum scour depth occurs before beginning of the bridge cresting. Although scour depth in submerged bridge without pier decreases after cresting in a short limited of submergence ratio from 0 to 0.08, it increases again as flow depth increase. Also, existence of a pier strongly affects the maximum scour depth around the flume wall which receives the deflected flow.